If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 3) = 2(4 + -1x) Reorder the terms: 3(3 + x) = 2(4 + -1x) (3 * 3 + x * 3) = 2(4 + -1x) (9 + 3x) = 2(4 + -1x) 9 + 3x = (4 * 2 + -1x * 2) 9 + 3x = (8 + -2x) Solving 9 + 3x = 8 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 9 + 3x + 2x = 8 + -2x + 2x Combine like terms: 3x + 2x = 5x 9 + 5x = 8 + -2x + 2x Combine like terms: -2x + 2x = 0 9 + 5x = 8 + 0 9 + 5x = 8 Add '-9' to each side of the equation. 9 + -9 + 5x = 8 + -9 Combine like terms: 9 + -9 = 0 0 + 5x = 8 + -9 5x = 8 + -9 Combine like terms: 8 + -9 = -1 5x = -1 Divide each side by '5'. x = -0.2 Simplifying x = -0.2
| 7x+2y-10x+5= | | 3(x-4)=2x-6 | | 12x(x-9)=0 | | 2(2x-3)=3(x-10) | | -5X+12=5X^2-12 | | N^3+n^2-6n=0 | | 14-7x=43-14x | | 2n^2+12n+15=-3 | | 2n^2+12n+15=3 | | 2n^2+n-120=0 | | 10x^2n+47xny+42y^2n=0 | | 5g+15=2g | | -4x^3-2x+1=0 | | 6x+38=14 | | 27u^2+54uv-21v^2=0 | | 1x-2y-3z=0 | | Y^2+4Y+11=0 | | (2x-3)(x^2-5x+3)=0 | | -8-3c=19 | | ln^2x+lnx=12 | | 10x^2-21x+2=0 | | 4x-12=-30 | | 144x^2-96x-84=0 | | s^2d^2+9sd+14= | | 2-ln(3-x)=0 | | 9x^2y^2-12x^2y^2-3x^2y^2= | | a^3+1000b^3=0 | | 3e^3=10 | | 4x^2-72x+299=0 | | 20x+30(100-x)=2350 | | 4(x)=215 | | x^3+14x^2=-49x |